Representation of scales and prosody proportions of Maulana Khalid Naqshbandi's Diwan based on Persian, Kurdish and Arabic poems - Seyed Asaad Sheikhahmadi; Sohila Salimizand (مطالعات زبانی و بلاغی)
Maulana Khalid Naqshbandi is one of the Sufi scholars, scholars, theologians, and Kurdish poets who, apart from numerous works in Islamic sciences, mysticism, and Sufism, in various poetic formats, including: odes, Maulana Khalid Naqshbandi is one of the Sufi scholars, scholars, theologians, and Kurdish poets who, apart from numerous works in Islamic sciences, mysticism, and Sufism, in various poetic formats, including: odes, poems, ghazals, and masnavis, poems in Persian and It is written in Kurdish and Arabic; In this research, the prosody weights of these poems have been examined and analyzed based on the standards and rules of prosody. The variety of prosody weights and the familiarity of this poet with various Persian and Arabic weights have revealed and highlighted the literary point of his poems. The obtained results show that the variety of prosody weights in his Persian poems is more than Kurdish and Arabic poems. The unique and beautiful point in his poems is that he has used the characteristic bahur of Arabic poetry in the composition of Persian masnavis, and he has benefited from the characteristic weights of the quartet poetry in the composition of the poetic forms of the piece and the sonnet. The weights of his Kurdish poems are syllabic and folkloric. He used his Sufi thoughts and beliefs in his Persian poems in the style of Iraqi style poets and used weights in their works.